Reducing physical restraint use in critically ill patients - Duwadi, Sona; Singh Budal, Birendra; Qing Hua, Zhao (International Journal of Endorsing Health Science Research, 2018)
Background: Patients in critical care setting often encounter severe delirium and agitation putting them at risk of harm. So it has become a common trend to restraint patient physically in intensive care units. However, physical restraint has several adverse physical, psychological and ethical consequences. Awareness regarding significant risk associated with physical restraint, continuing education and skills stabilize the patient’s safety and potential complication regarding ethical and legal issues to physical restraint in critical care settings. This study aims to address if any alternatives have been tested regarding physical restraint to improve the patient care for critical care. Methodology: A search conducted using the PubMed, Medline and Google Scholar including physical restraint use in critical care setting from 1994 to 2017. Studies published in English were included whereas articles published in psychiatric care, children and outside the hospital were excluded. The keywords used were critical care, critically ill, ICU patient safety and physical restraint. The Boolean phrases were used to clarify the quality of search results: ‘‘physical restraint & critical care,’’ ‘‘physical restraint & critically ill’’ ‘‘physical restraint & ICU,’’ physical restraint & patient safety.’’ Additionally, reference lists of selected papers were then evaluated further. Results: Enhanced knowledge, focused education and continuing training to improve skills in using restraint alternatives, awareness of the risk, early identification, conduct proper institutional policies and guidelines, and proactive intervention is the significant measures in alleviating physical restraint use in critical care settings. Conclusion: A restraint-free environment not only promotes patient safety but also ensure greater caregivers’ job satisfaction reducing ethical issues.